Functional reliability of a real-time redundant computational process in cluster architecture systems - Bogatyrev, V. A.; Bogatyrev, A. V. (Automatic control and computer sciences, 2015)
Functional reliability models are proposed for a real-time redundant computational process when an incoming request flow is distributed for redundant execution of request copies in several nodes of a cluster architecture system operating under conditions of faults, failures, and errors in nodes; in this case, the reliability, integrity, and timeliness of executing functional requests must be ensured. The effect of the organization and redundancy rate of computations on their timeliness and reliability, as well as on the average request waiting time, is analyzed taking into account faults, failures, and errors in cluster nodes.